2021
DOI: 10.3389/fpsyg.2021.713943
|View full text |Cite
|
Sign up to set email alerts
|

Using Artificial Intelligence-Based Collaborative Teaching in Media Learning

Abstract: With the advent of the 5G era, humans must not only learn the knowledge and skills of cross-border integration but must also get to grips with the breadth and efficiency of artificial intelligence (AI) technology in order to jointly overcome current difficulties and create a happy and beautiful life. In this article, we use the example of an elementary school to discuss the decision-making factors that influence teachers when choosing AI technology, where the digital content of schools is imported into artific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…These findings align with previous research (Bui & Nguyen, 2022;De Carlo et al, 2020;Malamateniou et al, 2021;Palomares et al, 2022;Pantanowitz et al, 2022;Paschen, 2020;Tao et al, 2019;Wang & Liu, 2021) by revealing the integration of artificial intelligence (AI) as a prominent trend. This reflects the global shift towards AI-driven marketing strategies to personalize customer experiences and optimize campaigns.…”
Section: Results and Dicussionsupporting
confidence: 92%
“…These findings align with previous research (Bui & Nguyen, 2022;De Carlo et al, 2020;Malamateniou et al, 2021;Palomares et al, 2022;Pantanowitz et al, 2022;Paschen, 2020;Tao et al, 2019;Wang & Liu, 2021) by revealing the integration of artificial intelligence (AI) as a prominent trend. This reflects the global shift towards AI-driven marketing strategies to personalize customer experiences and optimize campaigns.…”
Section: Results and Dicussionsupporting
confidence: 92%
“…e preference for music and its ability to stimulate the senses make it an important part of the human experience [20]. Using melodic complexity as a diagnostic tool, these studies show how melodic contingencies can be identified and which aspects of melody (pitch combinations, hierarchical structure and sequential order, and so on) are more important for parsing together melodic structures when parsing together melodic structures (similarity ratings, melodic repertoire, etc.)…”
Section: Introductionmentioning
confidence: 99%